Alteration of lipopolysaccharide O antigen leads to avirulence of gut-colonizing Serratia marcescens - Lee, Junbeom; Kim, Jong Uk; Lee, Bok Luel; Kim, Jiyeun Kate (Frontiers in Microbiology, 2023)
The reason why the potent entomopathogen Serratia marcescens fails to kill insects through oral infection is unknown. To compare effects of septic injection and oral administration of S. marcescens, we used a model bean bug, Riptortus pedestris. Most R. pedestris insects survived oral infections, but not septic infections. Although the number of S. marcescens cells in hemolymph after oral infection, which were originated from gut-colonizing S. marcescens, was higher than the fatal number of cells used in septic injection, they did not kill host insects, suggesting a loss of virulence in gut-colonizing S. marcescens cells. When gut-colonizing S. marcescens cells were septically injected into insects, they failed to kill R. pedestris and survive in hemolymph. To understand the avirulence mechanisms in gut-colonizing bacteria, lipopolysaccharides of S. marcescens were analyzed and revealed that the O antigen was lost during gut colonization. Gut-colonizing S. marcescens cells were resistant to humoral immune responses but susceptible to cellular immune responses, easily succumbing to phagocytosis of hemocytes. When cellular immunity was suppressed, the gut-colonizing S. marcescens cells recovered their virulence and killed insects through septic injection. These results suggest that a key mechanism of avirulence in orally infected S. marcescens is the loss of the O antigen, resulting in susceptibility to host’s cellular immune responses.